Urban/ Regional Co-Operation in Greece: Athens, a Capital City under the Shadow of the State - Harry Coccossis; Alex Deffner; Dimitris Economou (European Regional Science Association (ERSA), 2003)
The main purpose of the paper is to demonstrate the difficulty of urban/ regional co-operation in Greece focusing on the overshadowing of its capital Athens by the state. The main outcome of this process is the responsibility of many organisations and actors for the same issue, thus acting as a living proof of the proverb `too many cooks spoil the broth'. The first part of the paper presents the basic characteristics and trends in terms of the population, economy, society, environment, spatial structure, transport and international role of the Athens Metropolitan Area. On the basis of these some of the key problems are discussed, particularly in relation to the role of the metropolitan area at a national level. The second part involves an introduction to the basic policy context, particularly the one that has a major impact on the structure and function of the metropolitan area. Existing policies and programmes are briefly presented with a view to assess their influence on the potential role of the metropolitan area at a national context. There is also reference to selected case studies such as transport planning, water management and risk management (natural disasters e.g. earthquakes). The third part discusses the basic institutional context, i.e. the administrative and organizational arrangements and the way they influence the function and the role of the metropolitan area. The frame and the conditions of urban/ regional co-operation are analysed, a typical example being the problematic relationship between the private and the public sector: the public sector is unable to press the state and vice versa (e.g. the case of demanding permissions for new hotels in the saturated Athens Metropolitan Area because of the 2004 Olympics). The last part analyses the main scenarios for urban/ regional co-operation referring to the indications for innovative elements and to the prospects of various new fields for Greece such as place marketing and leisure planning (tourism, culture, sports). The focus of this paper is not on the documentation but rather on a synthesis of strengths and weaknesses, opportunities and threats for the metropolitan area in a national context.
Keywords: 330